PHYSIOLOGIC EFFECTS OF CONTINUOUS-FLOW LEFT VENTRICULAR ASSIST DEVICES - Healy, Aaron H. (J Surg Res, 2016)
BACKGROUND: Within the past ten years, continuous-flow Left Ventricular Assist Devices (LVADS) have replaced pulsatile-flow LVADs as the standard of care for both destination therapy and bridging patients to heart transplantation. Despite the rapid clinical adoption of continuous-flow LVADs, an understanding of the effects of continuous-flow physiology, as opposed to more natural pulsatile-flow physiology, is still evolving. MATERIALS AND METHODS: A thorough review of the relevant scientific literature regarding the physiologic and clinical effects of continuous-flow physiology was performed. These effects were analyzed on an organ system basis and include an evaluation of the cardiovascular, respiratory, hematologic, gastrointestinal, renal, hepatic, neurologic, immunologic, and endocrine systems. RESULTS: Continuous-flow physiology is, generally speaking, well tolerated over the long term. Several changes are manifest at the organ system level, however. While many of these changes are without appreciable clinical significance, other changes, such as an increased rate of gastrointestinal bleeding, appear to be associated with continuous-flow physiology. CONCLUSIONS: Continuous-flow LVADs confer a significant advantage over their pulsatile-flow counterparts with regard to size and durability. From a physiologic standpoint, continuous-flow physiology has limited clinical effects at the organ system level. Though improved over previous generations, challenges with this technology remain. Approaching these problems with a combination of clinical and engineering solutions may be needed to achieve continued progression in the field of durable mechanical circulatory support.